Computationally-guided optimization of small-molecule inhibitors of the Aurora A kinase–TPX2 protein–protein interaction. Issue 67 (8th August 2017) - Cole, Daniel J.; Janecek, Matej; Stokes, Jamie E.; Rossmann, Maxim; Faver, John C.; McKenzie, Grahame J.; Venkitaraman, Ashok R.; Hyvönen, Marko; Spring, David R.; Huggins, David J.; Jorgensen, William L.
Abstract : Computational binding free energy predictions were validated against experiment and used to design new inhibitors of an important protein–protein interaction. Abstract : Free energy perturbation theory, in combination with enhanced sampling of protein–ligand binding modes, is evaluated in the context of fragment-based drug design, and used to design two new small-molecule inhibitors of the Aurora A kinase–TPX2 protein–protein interaction.